Impacts of health education on knowledge and practice of hospital staff with regard to Healthcare waste management at White Nile State main hospitals, Sudan - Elnour, Ahmed Mohammed; Moussa, Mayada Mohamed Reda; El-Borgy, Mohamed Darwish; Fadelella, Nur Eldin Eltahir; Mahmoud, Aleya Hanafy (International Journal of Health Sciences, 2015)
Objectives: The present study aims at assessing nursing and sanitation staff knowledge and practice regarding Healthcare Waste (HCW) management before and after the implementation of an educational intervention program at the main hospitals of the White Nile State in Sudan. Methodology: Quasi-experimental study design was applied to assess the impact of an intervention program on knowledge and practice regarding HCW management. The same questionnaire used in the pre-test was used immediately after the end of the intervention program and then again three months later for a second post-test. Â Results: The results showed that the majority of nursing and sanitation staff had fair knowledge regarding HCW management before the educational intervention program (17% good, 58% fair, and 25% poor). After implementation of the educational program, the majority had good knowledge (56% good, 34% fair, and 10% poor) in the immediate post-test, and also in the post-test three months later (59% good, 35% fair, and 6% poor). More than half the nursing and sanitation staff had fair level of practice before the educational intervention program (42% good, 55% fair, and 3% poor). After the implementation of the intervention program, the immediate post-test showed a similar result (45% good, 54% fair, and 1% poor), while the post-test three months later showed that the majority demonstrated good practice level (55% good, 42% fair, and 3% poor). Â Conclusion: The nursing and sanitation staff at the main hospitals of the White Nile State in Sudan recorded significant improvement in their knowledge and practice with regard to HCW management immediately after the educational intervention program and three months later. Â